Landscape, body and waste in Los pies de San Juan, by Eduardo Lalo (Anclajes, 2021)
Los pies de San Juan by Eduardo Lalo is a hybrid work: it has been variously described as a photographic essay, an artist book, a chronicle-book, a performance album and a book-object. In this work emerges an obsession for detail and fragmentation, which makes it impossible to construct a global image of a San Juan of Puerto Rico that is explored on foot, camera at hand, in search of marks in the ground, waste and traces of decadence, rather than through panoramic views. This essay will analyze this sense of fragmentation and waste, taking into account the photographic repertoire but mainly focusing on the written reflections that accompany it. The cityscape is constructed as an “anti-postcard”, in which the parts selected never allow us to see a whole, and in which Lalo’s cosmovision of the subject “being” the city establishes a fusion between body and city.
Keywords: Puerto Rican Literature; Eduardo Lalo; landscape; city; fragmentation